Landscape genetics and behavioral ecology of Greater Prairie-Chickens (Tympanuchus cupido) - Gregory, Andrew J. (Kansas State University, 2011)
Anthropogenic activities and climate change have dramatically altered landscapes worldwide. The ability of species to cope and adapt to ongoing changes is likely a function of their behavior, movements, and sensitivity to fragmentation. Greater Prairie-Chickens (GPC) are a lek mating grouse native to the Great Plains Landscape Conservation Cooperative (GPLCC), for which inbreeding depression and anthropogenic avoidance are a concern. The goals of my dissertation were to: 1) identify genetic correlates of male performance which may influence population viability under current land use practices, 2) identify GPC habitat characteristics and delineate areas of critical GPC habitat necessary for GPC conservation, and 3) identify the relative importance of distance and habitat quality for maintaining genetic connectivity among spatially structured populations. First, I found male reproductive success and survival to be positively associated with genetic diversity. Using multistate modeling in Program Mark, male survival across the observed range of variation in number of alleles (15-22) increased more than fourfold from 0.17 to 0.77. Second, I found 35-40% of Kansas, and 1.5 % (11,000 Km squared) of the GPLCC, were considered high-quality lek habitats. Top performing logistic models predicting lek presence (wi=0.95) included strong effects of grassland cover and avoidance of anthropogenic disturbance. When this model was applied to putative future landscapes based on climate change and current land use trends over a 70-year period, I found a 27-40% reduction in habitat area and a 137 Km southeast shift in habitat distribution. Under equilibrium conditions we expect isolation by distance (IBD) to explain the distribution of genetic diversity. However, if the landscape restricts dispersal, then we might observe isolation by resistance (IBR). I used model selection procedures to choose among competing IBR or IBD models to explain the distribution of genetic diversity among GPC populations across Kansas and the GPLCC. IBD was never supported (R-square<0.02, P>0.09). The best models for Kansas (R2=0.69, P<0.02) and for the GPLCC (R-square=0.46, P<0.02) indicated that human-mediated landscape changes have influenced landscape permeability for dispersal. The integration of behavioral, landscape, and genetic data provided new insights on prairie-chicken ecology, and is a powerful approach for developing conservation strategies for sensitive species.
Keywords: Landscape genetics; permeability modeling; Behavioral Ecology; Animal Sciences (0475); Biology (0306); Ecology (0329)